2008
DOI: 10.1063/1.2889501
|View full text |Cite
|
Sign up to set email alerts
|

Microwave guiding in air by a cylindrical filament array waveguide

Abstract: Microwave guiding was demonstrated over 16cm in air using a large diameter hollow plasma waveguide. The waveguide was generated with the 100TW femtosecond laser system at the Advanced Laser Light Source facility. A deformable mirror was used to spatially shape the intense laser pulses in order to generate hundreds of filaments judiciously distributed in a cylindrical shape, creating a cylindrical plasma wall that acts as a microwave waveguide. The microwaves were confined for about 10ns, which corresponds to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
64
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(64 citation statements)
references
References 25 publications
0
64
0
Order By: Relevance
“…5(d), where its peak intensity is found to be ~ 250 times that of a single filament. Recently, M. Châteauneuf and coworkers have reported the generation of 10 3 filaments organized in a circle [26]. With proper phase control, it could lead to a 10 6 increase of THz peak intensity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5(d), where its peak intensity is found to be ~ 250 times that of a single filament. Recently, M. Châteauneuf and coworkers have reported the generation of 10 3 filaments organized in a circle [26]. With proper phase control, it could lead to a 10 6 increase of THz peak intensity.…”
mentioning
confidence: 99%
“…The good agreement between our experimental observations and calculations validates the theoretical model and permits to extrapolate the results to a higher number of filaments. It has been demonstrated that a large number of filaments can be organized in regular patterns by manipulation of the beam profile of a femtosecond laser pulse with P >> P cr [24][25][26]. We have calculated the THz radiation distribution for N = 4, 6, 8, 9, 12, 16 filaments organized in a square grid.…”
mentioning
confidence: 99%
“…Experimental data about the long term dynamics is especially scarce. The filamenting pulse leaves behind free electrons at initial densities of 10 16 -10 17 cm -3 [2,3], mostly from multi-photon ionization of oxygen molecules because the ionization potential of N 2 molecules is significantly larger (12 eV and 16 eV for O 2 and N 2 , respectively). Initially, the free electron density exhibits a radial bell-shape profile.…”
mentioning
confidence: 99%
“…A pioneer work demonstrated the feasibility of radiofrequency (RF) plasma using a nanosecond laser to induce a discharge in air 1 . More recently attention has been paid to the potentiality of femtosecond filamentation for guiding microwave radiation under atmospheric conditions [9][10][11][12] . During filamentation [13][14][15] a weakly ionized plasma column is created in the wake of an intense fs laser pulse, with an initial electron density of ~ 10 16 cm -3 , a  100 µm diameter and a nanosecond recombination time 16 .…”
mentioning
confidence: 99%